INFORMATION FOR FUTURE PRIMARY TEACHERS ORGANIZE COMPETENCE DEVELOPMENT METHODOLOGY ACHIEVE - Boymurodova Sarvinoz Saparali kizi (Bright Mind Publishing, 2025)
In the article, the system of developing the information competence of teachers in the Republic of Uzbekistan and the methods of its application in the organization of an effective educational system, its importance, problems, models of information competence and their types are detailed.
Keywords: Teacher's information competence, educational models, professional knowledge, computer literacy, information environment.